Penerapan Lesson Study dan Moodle untuk Meningkatkan Keterampilan Proses Belajar - Rizqi Amaliyakh Sholikhakh; Dian Nataria Oktaviani; Herani Tri Lestiana (Procediamath, 2018)
Application of Lesson Study and Moodle to Improve Learning Process SkillsEmphasizing the process of learning is very important because the learning process will determine learning outcomes. The learning process can provide learning experiences to students so that learning will be more meaningful. Moodle is an application of the concepts and mechanisms of teaching and learning that utilize information technology. The purpose of this research was to describe the application of Moodle-assisted Lesson Study to improve learning process skills at Evaluation Process and Mathematics Learning Outcomes course. The research subjects were 30  students of 4th semester in Mathematics Education Study Program Faculty of Teacher Training and Education of  Pancasakti University 2017/2018 academic year. The research process was carried out through 3 cycles. Each cycle consists of three stages: plan, do, see. Data collection techniques through interviews, observation, and documentation. Data analysis techniques are carried out by data collection processes according to Milles and Humberman. The results of the research were obtained  the improvement of the learning process in Evaluation Process and Mathematics Learning Outcomes Course.